Rasisme dalam Film Lee Daniels, The Butler - Syamsul Bahri; Zefanya Putra Julu Manullang; Novita Sari Hutapea (Pusat Riset dan Inovasi Nasional, 2022)
The Butler movie explored discrimination between white and black people that created social grade which lead to the conflict. This became a very interesting one to explore. The purpose of this study was to find more about the racism in such movie. The researcher used a qualitative descriptive method, and the research material was a dialogue from the movie